2003
DOI: 10.1194/jlr.m300251-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The APOA5 locus is a strong determinant of plasma triglyceride concentrations across ethnic groups in Singapore

Abstract: Singapore comprises three ethnic groups: Chinese (76.7%), Malays (14%), and Asian-Indians (7.9%). Overall, Singaporeans experience coronary heart disease rates similar to those found in the United States. However, there is a dramatic interethnic gradient, with Asian-Indians having significantly higher risk than Chinese and Malays. These differences are associated with HDL cholesterol levels and cannot be solely explained by environmental exposure, and may be driven by genetic factors. The gene encoding apolipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
105
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 22 publications
17
105
3
Order By: Relevance
“…33,34 Pervious studies reported that the allele frequency ranged from 6 to 8% for Caucasian and Africans, 1,4,7 from 4 to 8% in African Americans, 4,35 was 15% in Hispanics 4,7 and was very rare, that is, 1-3%, in Chinese and Japanese. 10,31,32 The frequencies of the other four SNPs ranged from 9 to 11% for Caucasians, 4,7 13 to 16% for Hispanics, 4,36 6 to 9% for African Americans 1,4 and are in common frequencies of 27 to 37% among East Asian populations. 10,31,[36][37][38] Although all four common polymorphisms at the ApoA5 locus were associated with plasma TG concentrations in Yemenite and Ashkenazi, the possibility that any one of them represents a functional variant is very small because; they are in a strong LD with one or more functional variants that directly affect the TG plasma concentration.…”
Section: Snps/haplotypes and Plasma Tg Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…33,34 Pervious studies reported that the allele frequency ranged from 6 to 8% for Caucasian and Africans, 1,4,7 from 4 to 8% in African Americans, 4,35 was 15% in Hispanics 4,7 and was very rare, that is, 1-3%, in Chinese and Japanese. 10,31,32 The frequencies of the other four SNPs ranged from 9 to 11% for Caucasians, 4,7 13 to 16% for Hispanics, 4,36 6 to 9% for African Americans 1,4 and are in common frequencies of 27 to 37% among East Asian populations. 10,31,[36][37][38] Although all four common polymorphisms at the ApoA5 locus were associated with plasma TG concentrations in Yemenite and Ashkenazi, the possibility that any one of them represents a functional variant is very small because; they are in a strong LD with one or more functional variants that directly affect the TG plasma concentration.…”
Section: Snps/haplotypes and Plasma Tg Concentrationmentioning
confidence: 99%
“…10,31,32 The frequencies of the other four SNPs ranged from 9 to 11% for Caucasians, 4,7 13 to 16% for Hispanics, 4,36 6 to 9% for African Americans 1,4 and are in common frequencies of 27 to 37% among East Asian populations. 10,31,[36][37][38] Although all four common polymorphisms at the ApoA5 locus were associated with plasma TG concentrations in Yemenite and Ashkenazi, the possibility that any one of them represents a functional variant is very small because; they are in a strong LD with one or more functional variants that directly affect the TG plasma concentration. Several other polymorphisms in the ApoC-III gene have been shown to be associated with plasma TG concentration in different studies, 39 the most prominent being SNP 1100C4T in axon 3.…”
Section: Snps/haplotypes and Plasma Tg Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2a shows the results of the meta-analysis of our findings on rs662799 together with previous reports on healthy Chinese subjects. [19][20][21][22][23][24][25] The combined estimate of the standardized mean difference in plasma triglyceride level between the TT and CC genotypes was 0.58 (95% CI: 0.43-0.74) in a random effects model. In a meta-analysis of four studies on healthy European subjects with sample sizes greater than 300, [26][27][28][29] the corresponding estimate between TT and TC/CC genotypes was 0.33 (95% CI: 0.24-0.43) (Figure 2b).…”
Section: Association With Plasma Triglyceridesmentioning
confidence: 99%